DEMOGRAPHIC FACTORS ASSOCIATED WITH ANXIETY AMONG PREGNANT WOMEN OF POST-PANDEMIC COVID-19 IN CENTRAL KALIMANTAN - Thyrister Nina Asarya Sembiring; Muhammad Abdan Shadiqi; Mohammad Bakhriansyah; Syamsul Arifin; Silvia Kristanti Tri Febriana (The Indonesian Journal of Public Health, 2025)
Introduction: Anxiety in the 3rd trimester of pregnant women increased during the COVID-19 pandemic, ranging from 45.9% to 62% and occurs due to either a maturity crisis or a fear of childbirth. It has an impact on the health of the mother and the fetus. A preliminary study at a private mother and children hospital in Palangka Raya in December 2022 showed that 7 out of 10 3rd trimester pregnant women experienced anxiety. Aims: to analyze the relationship between parity, education level, employment status, and income with anxiety level among 3rd trimester pregnant women at a private mother and children hospital in Palangka Raya post-pandemic COVID-19. Method: An observational study with a cross-sectional approach and a representative sample size was 255 respondents from 3rd trimester pregnant women using a non-probability sampling method and a questionnaire as the research instrument. Odds Ratios (ORs) and 95% Confidence Intervals (95% CIs) were calculated by using Multinomial Logistic Regression analyses. Results: Higher education was significantly associated with a low anxiety level (adj. OR 0.266, 95%CI 0.094-0.786; p= 0.012) as well as low income with moderate anxiety of 3rd trimester pregnant women (adj. OR 0.121, 95%CI 0.024-0.613; p=0.011). Conclusion: There is a relationship between education level as well as income and anxiety among 3rd trimester pregnant women at a private mother and children hospital in Palangka Raya.